1999
DOI: 10.1007/bf02359994
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the structure of structural steel on its corrosion in acidic media

Abstract: The structural state of structural steels with various strengths influences their corrosion under both hydrogen and oxygen depolarization [1].For example, with increase in the amount of pearlite, i.e., with increase in the carbon content of a hot-rolled metal from 0.5 to 0.8%, the corrosion activity of rolled metals in acidic media sharply increases [2]. In such a medium, at the same strength, steel with laminated carbides is characterized by a higher corrosion wear than steel with globular carbides [3].Modem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…[35] investigated the effects of grain size on the corrosion resistance of high-nitrogen steel by immersion corrosion and potentiodynamic polarisation measurement and found that grain refinement reduced the rate of intergranular corrosion and pitting corrosion, but increased the uniform corrosion rate. Kalmykov and Razdobreev [36] studied the influence of grain size on carbon steel in 3% NaCl solution by cyclic dry/wet laboratory tests and showed that the corrosion rate of the sample with grain size 15.8 µm is less than that of the sample with grain size 68.0 µm. Osório et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[35] investigated the effects of grain size on the corrosion resistance of high-nitrogen steel by immersion corrosion and potentiodynamic polarisation measurement and found that grain refinement reduced the rate of intergranular corrosion and pitting corrosion, but increased the uniform corrosion rate. Kalmykov and Razdobreev [36] studied the influence of grain size on carbon steel in 3% NaCl solution by cyclic dry/wet laboratory tests and showed that the corrosion rate of the sample with grain size 15.8 µm is less than that of the sample with grain size 68.0 µm. Osório et al.…”
Section: Resultsmentioning
confidence: 99%
“…Di Schino et al [35] investigated the effects of grain size on the corrosion resistance of high-nitrogen steel by immersion corrosion and potentiodynamic polarisation measurement and found that grain refinement reduced the rate of intergranular corrosion and pitting corrosion, but increased the uniform corrosion rate. Kalmykov and Razdobreev [36] studied the influence of grain size on carbon steel in 3% NaCl solution by cyclic dry/wet laboratory tests and showed that the corrosion rate of the sample with grain size 15.8 µm is less than that of the sample with grain size 68.0 µm. Osório et al [34] investigated the effects of grain size on corrosion resistance of zinc and aluminium castings by potentiodynamic polarisation measurement and EIS and found that the corrosion resistance of the specimen with coarse grains is better than that of the specimen with fine grain.…”
Section: Fementioning
confidence: 99%
“…along with the amount and forms of the cementite precipitates [1][2][3][4][5][6][7][8][9][10][11]. A great deal of works is dedicated to the effects of the most commonly used metallurgical impurities (sulfides, oxides, etc.)…”
Section: Introductionmentioning
confidence: 99%